La incrementación del robo agravado y su repercusión social en la región San Martin durante los años 2020 - 2021 - Caballero Grandez, Wagner (2023)
Within our social reality, the increase in criminal crime rates and the high perception of citizen insecurity by Peruvians are becoming increasingly important. For this reason, this study sought to identify the various social factors that are involved in the increase in crime rates and the greater social rejection towards them, taking the San Martín region as our geographical space of investigation in the temporary period of the year. 2020 to 2021. For this, explanatory research was used in order to explain the reasons for the increase in aggravated robbery and its social impact in the San Martín region during the years 2020 - 2021. This was contrasted with the application of surveys to 20 legal operators. of the San Martín region, as well as the analysis of 10 files of aggravated robbery of the Superior Court of Justice of San Martín. Finally, the results of this research work denote a high perception of citizen insecurity in the San Martín region, as well as a high criminal incidence to the detriment of citizens.